Micronization of Low-Salinity Baltic Sea Blue Mussels: Enhancing Whole-Biomass Utilization and Nutritional Viability - Indrek Adler; Jonne Kotta; Kristel Vene (Fishes)
The micronization of low-salinity Baltic Sea blue mussels (Mytilus edulis/trossulus) was investigated as a novel valorisation pathway to eliminate the need for labor-intensive meat–shell separation. The small size of Baltic mussels poses a challenge for traditional meat–shell separation. This study investigates micronization as an alternative processing approach to enhance biomass utilization while preserving functional and nutritional properties. This study assessed the feasibility of whole-mussel micronization, focusing on its impact on particle size distribution, grittiness, and the potential separation of meat and shell fractions post-processing. The results demonstrated that micronization at 4000 rpm resulted in a fine powder (<63 µm), significantly reducing grittiness. However, mild chalkiness was observed at higher concentrations (4% solution), highlighting the need for formulation adjustments. While it was expected to facilitate the separation of soft tissue from shell material, the results indicated that this remained impractical due to structural or compositional similarities at finer scales. A sensory evaluation of the whole-mussel powder assessed its texture and palatability, revealing its potential suitability for functional food applications. The findings highlight the potential of micronization as a resource-efficient and scalable processing method, enhancing the economic and environmental value of Baltic mussels in the food industry.